Tree monoculture plantations decrease plant diversity in the Italian Prealps - Vanessa Manuzi; Simone Balestra; Pietro Gatti; Gianalberto Losapio (Ecological Solutions and Evidence, 2025)
Abstract On the one hand, afforestation and reforestation can contribute to mitigate climate change impacts via carbon sequestration. On the other hand, these actions can also have counteractive effects on ecological systems by negatively affecting biodiversity. However, the long‐term consequences of afforestation and reforestation for biodiversity are poorly understood. We address the long‐term, centennial impact of afforestation and reforestation policies dated 1920s in Italian Prealps, which were implemented with tree monoculture of spruce (Picea abies). We conducted a comparative study examining changes in plant diversity and community composition along with environmental factors (i.e. luminosity and ground surface temperature) among spruce monoculture plantations, native deciduous mixed forests and pastures. Our results reveal the long‐lasting impact of afforestation and reforestation on biodiversity. Spruce monoculture plantation decreases plant species richness by 39% and 56% as compared to native mixed forest and pasture, respectively. Likewise, the diversity of plant growth forms, including trees and understorey shrubs and herbs, decreases in spruce plantation as compared to mixed forests or pastures. We also found a generally positive relationship between plant diversity and both luminosity and ground surface temperature, environmental factors that are lower in spruce plantations than pastures. Considering beta diversity, spruce monoculture plantations exhibited higher species turnover than species replacement, reflecting a shift in species composition rather than a simple reduction in diversity. Our research provides novel evidence that tree monoculture plantations negatively impact biodiversity still 100 years after planting trees. We report evidence that tree plantations do not merely filter out species but actively restructure communities, causing species loss and shifts in functional composition. As biodiversity loss and climate change are two interwoven processes, they must not be treated separately. Solution. In the Italian Prealps, spruce monoculture plantations should be actively converted into native mixed forests. For what concerns future afforestation and reforestation programmes generally, we recommend that they include biodiversity‐driven actions and address win–win solutions by adopting a diversified set of native species, for their effectiveness in climate change mitigation would otherwise be compromised.